Multidimensional carbon allotropes as electrochemical detectors in capillary and microchip electrophoresis. Issue 1 (27th October 2014) - Martín, Aída; López, Miguel Ángel; González, María Cristina; Escarpa, Alberto; El Rassi, Ziad
<x xml:space="preserve">Abstract</x> The main multidimensional carbon allotropes could be classified into carbon nanotubes as 1D material, graphene as 2D material, as well as graphite and diamond as 3D carbon materials. Along with this review, a discussion using these four structures as electrochemical detectors in CE and ME will permit us to explore the recent advances in this field.